2017
DOI: 10.1371/journal.pone.0180775
|View full text |Cite
|
Sign up to set email alerts
|

Identification of odorant binding proteins and chemosensory proteins in Microplitis mediator as well as functional characterization of chemosensory protein 3

Abstract: Odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play important roles in transporting semiochemicals through the sensillar lymph to olfactory receptors in insect antennae. In the present study, twenty OBPs and three CSPs were identified from the antennal transcriptome of Microplitis mediator. Ten OBPs (MmedOBP11–20) and two CSPs (MmedCSP2–3) were newly identified. The expression patterns of these new genes in olfactory and non-olfactory tissues were investigated by real-time quantitative PCR (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…An analysis of the expression patterns of CSPs, indicated that exploration of the functions of CobdCSP14 and CobdCSP3 in antenna and other tissues will be important. Some CSPs were significantly expressed in antennae, including most of the CSPs of Lobesia botrana (Rojas et al, 2018) and MmedCSP2 and MmedCSP3 of Microplitis mediator (Peng et al, 2017). MmedCSP3 can bind insect odors and plant volatiles, as well as pheromone components of Noctuidae, Z11-16:Ald, Z11-16: OH and E11-14:Ac (Peng et al, 2017), illustrating the binding ability and functions of CSPs in olfactory recognition.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An analysis of the expression patterns of CSPs, indicated that exploration of the functions of CobdCSP14 and CobdCSP3 in antenna and other tissues will be important. Some CSPs were significantly expressed in antennae, including most of the CSPs of Lobesia botrana (Rojas et al, 2018) and MmedCSP2 and MmedCSP3 of Microplitis mediator (Peng et al, 2017). MmedCSP3 can bind insect odors and plant volatiles, as well as pheromone components of Noctuidae, Z11-16:Ald, Z11-16: OH and E11-14:Ac (Peng et al, 2017), illustrating the binding ability and functions of CSPs in olfactory recognition.…”
Section: Discussionmentioning
confidence: 91%
“…Some CSPs were significantly expressed in antennae, including most of the CSPs of Lobesia botrana (Rojas et al, 2018) and MmedCSP2 and MmedCSP3 of Microplitis mediator (Peng et al, 2017). MmedCSP3 can bind insect odors and plant volatiles, as well as pheromone components of Noctuidae, Z11-16:Ald, Z11-16: OH and E11-14:Ac (Peng et al, 2017), illustrating the binding ability and functions of CSPs in olfactory recognition. CSPs of Diptera constitute an order-specific clade in the CSP phylogenetic tree, which was the same as Mamestra brassicae (Jacquinjoly et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Combined with the high expression of DarmCSP2 in antennae and mouthparts, these data suggest that DarmCSP2 may be a major carrier of the tested ten host volatiles and four pheromones of D. armandi . Data on CSPs in diverse insects also support this binding function: the proteins bind pheromone components in Schistocerca gregaria (Li et al, 2015 ), host plant volatiles and non-volatile secondary metabolites in Apolygus lucorum (Hua et al, 2012 ), as well as host plant volatiles and sex pheromones in Sesamia inferens and Microplitis mediator (Zhang et al, 2014 ; Peng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…This is partly solved in the insect olfactory system which employs strategies of combinatorial coding to process general odours as well as labelled lines for specific compounds from their host that need an immediate response (Haverkamp et al 2018). The capacity to sense the BVOC signals from their specific host plant is important for forest herbivores such as bark beetles (Progar et al 2014) and their enemies (Peng et al 2017). The perception of BVOCs by an insect antenna takes place on odour-perceiving sensilla hairs.…”
Section: Sensing Of Bvoc Signalsmentioning
confidence: 99%
“…A BVOC molecule enters the sensilla through cuticular pores. In the sensilla, lymph odour-binding proteins transport the BVOC molecule to the chemosensory receptor proteins on the dendrite of the olfactory receptor neuron, which transmits information further to the brains (Peng et al 2017). There are two types of olfactory sensory receptors; a broadly tuned receptor detects several dozen different compounds, and highly selective receptors are tuned to odours of outstanding ecological relevance (Haverkamp et al 2018).…”
Section: Sensing Of Bvoc Signalsmentioning
confidence: 99%